A UV and X-ray dual photochromic Zn (II) metal-organic framework based on viologen: Photo-controlled luminescence and temperature-dependent phosphorescence. (December 2022) - Xiao, Tong; Shi, Yong-Sheng; Yang, Dong-Dong; Zheng, Han-Wen; Fang, Yu-Hui; Liang, Qiong-Fang; Zheng, Xiang-Jun
Abstract: Nowadays, photoactive viologen units have been widely encapsulated in metal-organic frameworks and assembled into multifunctional materials with photochromism and other light regulating properties. A novel host-guest MOF material, {[Zn(bcbpy)0.5 (IPA)]·CH3 CN}n (1 ), has been constructed by a viologen ligand 1, 1′-bis((3-carboxylatobenzyl)-4, 4′-bipyridinium)-dichloride (H2 bcbpy·2Cl), isophthalic acid (IPA) and zinc(II) chloride. Complex 1 exhibits UV and X-ray dual photochromism and photo-controlled luminescence properties. Complex 1 also exhibits a temperature-dependent phosphorescence from cyan to yellow when the temperature increases from 77 to 297 K. 1T will be obtained when 1 is heated in air at 230 °C for 30 min, 1T shows less sensitive photochromic property than 1 due to its longer C–H⋯O hydrogen bond distance for electron transfer pathway. In addition, complex 1 has the potential application as an inkless and erasable printing material due to the excellent photochromic property. Graphical abstract: Image 1 Highlights: A UV and X-ray dual photochromic complex 1 was synthesized and characterized. Complex 1 exhibits photo-controlled luminescence properties. Complex 1 exhibits temperature-dependent phosphorescence properties. Complex 1 has the potential to be used as an inkless and erasable printing material.